Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17186810
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia Concurrent with Metabolic Syndrome Is Independently Associated with Chronic Kidney Disease among Community-Dwelling Adults in an Urban Korean Population

Abstract: Elevated homocysteine (Hcy) levels and metabolic syndrome (MetS) are associated with chronic kidney disease (CKD). We investigated the combined effects of hyperhomocysteinemia (HHcy) and MetS on CKD among community-dwelling adults in an urban area of South Korea. We also identified the combination of HHcy and individual MetS components associated with the maximal risk of CKD. A retrospective cross-sectional study involving 19,311 health examinees between 2 January 2011 and 31 December 2015 was conducted. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although BMI, serum cholesterol, and high blood pressure are traditional risk factors for cardiovascular disease and mortality in the general population, in patients with CKD with regards to Hcy, the results of prior studies reveals the effect of reverse epidemiology in these traditional risk factors [18,31]. Although HCY is known to be increased in CKD patients [32,33], ndings regarding whether it is an independent risk factor for increasing CVD risk in CKD patients are inconclusive [34][35][36][37]. In two studies with 367 and 88 hemodialysis patients, respectively, the low Hcy level in ESRD patients was observed to increase CVD outcome [38,39]; moreover, Hcy also showed a reverse epidemiology pattern as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMI, serum cholesterol, and high blood pressure are traditional risk factors for cardiovascular disease and mortality in the general population, in patients with CKD with regards to Hcy, the results of prior studies reveals the effect of reverse epidemiology in these traditional risk factors [18,31]. Although HCY is known to be increased in CKD patients [32,33], ndings regarding whether it is an independent risk factor for increasing CVD risk in CKD patients are inconclusive [34][35][36][37]. In two studies with 367 and 88 hemodialysis patients, respectively, the low Hcy level in ESRD patients was observed to increase CVD outcome [38,39]; moreover, Hcy also showed a reverse epidemiology pattern as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Growth differentiation factor 15 (GDF-15) is an endocrine factor involved in metabolism, and GDF-15 levels have been found to be significantly increased in elderly MetS patients and has been independently correlated with MetS (103,104). A study from the Japanese found that urinary A-megalin is associated with the clustering number of MetS traits including hyperhomocysteinemia (105,106). At present, Urinary podocyte-derived EVs (pEVs) is widely recognized as a specific biomarker for podocyte injury, and studies have found that it is significantly increased in secondary podocytes, such as early diabetic nephropathy, hypertensive nephropathy, and eclampsia (107)(108)(109).…”
Section: Diagnosis Of Mets-related Renal Injurymentioning
confidence: 99%
“…Although BMI, serum cholesterol, and high blood pressure are traditional risk factors for cardiovascular disease and mortality in the general population, in patients with CKD with regards to Hcy, the results of prior studies reveals the effect of reverse epidemiology in these traditional risk factors. [32] Although Hcy is known to be increased in CKD patients, [33,34] findings regarding whether it is an independent risk factor for increasing CVD risk in CKD patients are inconclusive. [35][36][37][38] In 2 studies with 367 and 88 hemodialysis patients, respectively, the low Hcy level in ESRD patients was observed to increase CVD outcome; moreover, Hcy also showed a reverse epidemiology pattern as mentioned above.…”
Section: Tablementioning
confidence: 99%